1999
DOI: 10.1177/0739986399214004
|View full text |Cite
|
Sign up to set email alerts
|

Identity and Career Choice among Mexican American and Euro-American Preservice Bilingual Teachers

Abstract: This article discusses an investigation that explored the relationship between the ethnic identity and career choice of Mexican American and Euro-American Spanish bilingual teaching candidates. In-depth interviews with 6 Mexican American and Euro-American preservice bilingual teaching candidates respectively were analyzed to determine their reference group orientation, affiliative identity, and rationale for becoming a bilingual teacher. Mexican American bilingual teaching candidates indicated a strong referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…In separate investigations, teacher candidates of color reported that serving as a role model for students of color was the primary reason for their wanting to teach (Guyton et al 1996;Jones et al 1999). More recently, Ochoa (2007) found that serving as a role model for Latino students was of central importance to Latino teachers.…”
Section: Teachers Of Color Serve As Role Models For All Studentsmentioning
confidence: 96%
“…In separate investigations, teacher candidates of color reported that serving as a role model for students of color was the primary reason for their wanting to teach (Guyton et al 1996;Jones et al 1999). More recently, Ochoa (2007) found that serving as a role model for Latino students was of central importance to Latino teachers.…”
Section: Teachers Of Color Serve As Role Models For All Studentsmentioning
confidence: 96%
“…Within the larger context of studies on preservice teacher education, however, there is an emergent body of research that aims to amplify the voices of racial and linguistic minority preservice teachers (for examples, see Arce, 2004;Burant, 1999;Clark & Flores, 2001;Galindo, 1996;Guerrero, 2003;Jones, Young, & Rodríguez, 1999;Kornfeld, 1999;Meacham, 2000;Pailliotet, 1997;Sheets & Chew, 2002;Tellez, 1999;Zitlow & DeCoker, 1994). A common thread among these studies is the apparent mismatch between the student's own culture and that of the academic institution.…”
Section: Racial and Linguistic Diversity In Teacher Education Literaturementioning
confidence: 97%
“…As future teachers, they see themselves as maintaining the language and culture of their affinity group. Further, these Latino aspirant teachers are acutely aware of the function that they will serve as role models for minority students and that they are examples of successful bilingual bicultural individuals (Jones et al 1999). Hence, Latinos choosing teaching as a profession are motivated by a strong commitment to social justice for Latino students (Flores et al 2011).…”
Section: Career Preferencementioning
confidence: 99%
“…Interestingly, Latino undergraduates often choose the teaching career due to their strong ethnic identity and group affinity (Jones et al 1999). As future teachers, they see themselves as maintaining the language and culture of their affinity group.…”
Section: Career Preferencementioning
confidence: 99%